Effect of humidity on tropospheric received signal strength (RSS) in ultra-high frequency (UHF) band - Roslan, U.; Mat, R.; Sabri, N.H.; Ahmad, S.; Zafar, S.N.A.S.; Omar, A.; Mustafa, W.A. (2020)
The variation of weather conditions can affect the performance and quality of a communication system and sensor network. Therefore, it is vital to explore the factors that influence the quality of the radio signal to adapt to weather conditions. This paper describes the tropospheric effect of the meteorological parameter (humidity) for Ultra High Frequency (UHF) band at KUSZA Observatory (KO), UniSZA, Terengganu. Received signal strength (RSS) and humidity were collected using spectrum analyser and weather station respectively for hours in a rainy and a sunny day. Statistical analysis was used to determine the relationship between humidity and RSS. The results show that variation in humidity conditions give RSS with negative correlations in both conditions. The correlation of the RSS and humidity at both observation days (rr =correlation of frequencies on rainy day, rs = correlation of frequencies on sunny day) for frequency . MHz (rr =-0.423, rs =-0.382), while for frequency 945 MHz (rr = -0.512, rs =-0.631), frequency 1867.5 MHz (rr =-0.588, rs =-0.669) and frequency 2160 MHz (rr = -0.509. rs =-0.805). This study will benefit the active spectrum users such as mobile telecommunications, wireless signal, satellite transmission TV and radio astronomy expert in the management of radio frequency interference (RFI) for the observation and monitoring of the radio signal transmission.